Sexual Differences in response to Mid- or Low-Premixed Insulin Analogue in Patients with Type 2 Diabetes - Bing-li Liu; Xiao-mei Liu; Yi-fei Ren; Yi-Xuan Sun; Meng-hui Luo; Lei Ye; Jian-hua Ma; Feng-fei Li (Journal of Diabetes Research)
Objective. To observe whether there are sexual-related differences in response to mid- or low-premixed insulin in type 2 diabetic patients. Methods. This was an analysis of CGM data of a previous study. After screening, patients with longstanding T2D receive a 7-day continuous subcutaneous insulin infusion (CSII) therapy, and then subjects were randomly assigned 1 : 1 into two groups receiving Novo Mix 30 or Humalog Mix 50 regimen for a 2-day phage, followed by a 4-day cross-over period. A 4-day continuous glucose monitoring (CGM) was performed during the cross-over period. The primary endpoint was the differences in glycemic control between male and female patients receiving mid- or low-premixed insulin therapy. Results. A total of 102 patients (52 men and 50 women) completed the study. Our data showed that male patients had significant decrease in mean glucose levels monitored by CGM after three meals during Humalog Mix 50 treatment period compared to those received Novo Mix 30 regimen (0900: 11.0±2.5 vs. 12.2±2.8, 1000: 9.9±2.9 vs. 11.3±3.1, 1200: 8.0±1.9 vs. 9.1±2.5, 1400: 9.2±2.3 vs. 10.3±2.5, and 2000: 7.3±2.1 vs. 8.2±2.4 mmol/L, p<0.05, respectively). In addition, male patients receiving Novo Mix 30 experienced a significantly increased hypoglycemic duration compared to those of receiving Humalog Mix 50 (0 (0, 4.8) vs. 0 (0, 0), p<0.05). Conclusion. Our data indicate that male patients with T2D receiving mid-premixed insulin analogue regimen may have a potential benefit of improvement in glycemic control compared to female patients. This trial is registered with ClinicalTrials.gov ChiCTR-IPR-15007340.